DISPARITAS PEMIDANAAN STUDI KASUS TINDAK PIDANA NARKOTIKA DI PENGADILAN TINGGI DENPASAR - Kadek Rahayu Purwaningsih. M (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2025)
This study aims to: (1) examine the factors that cause sentencing disparities in narcotics crime cases at the Denpasar High Court, and (2) identify and analyze the efforts made by law enforcement officials to prevent sentencing disparities. This research uses an empirical legal research method with a descriptive research. The study was conducted at the Denpasar High Court. Data were collected through document study and interviews with judges who handled Case Number 63/Pid.Sus/2024/PT Dps and Case Number 2/Pid.Sus/2024/PT Dps. The sampling technique applied was non-probability sampling with a purposive sampling type. The results of this research show that: (1) sentencing disparity occur due to the absence of binding sentencing guidelines, the discretionary power of judges, subjective factors and individual character of the judges, and the different circumstances of defendants in each case. (2) Efforts made by law enforcement authorities to prevent sentencing disparity include providing rational and transparent legal considerations, strengthening judicial ethics and professionalism, and encouraging academic and public discourse as a form of social contro